Metabolic syndrome signs in Wistar rats submitted to different high-fructose ingestion protocols - de Moura, Rodrigo Ferreira [UNESP]; Ribeiro, Carla [UNESP]; de Oliveira, Juliana Aparecida; Stevanato, Eliane; de Mello, Maria Alice Rostom [UNESP] (Cambridge University Press (CUP), 2009)
In search of an adequate model for the human metabolic syndrome, the metabolic characteristics of Wistar rats were analysed after being submitted to different protocols of high fructose ingestion. First, two adult rat groups (aged 90 d) were studied: a control group (C1; n 6) received regular rodent chow (Labina, Purina) and a fructose group (F1; n 6) was fed on regular rodent chow. Fructose was administered as a 10 % solution in drinking water. Second, two adult rat groups (aged 90 d) were evaluated: a control group (C2; n 6) was fed on a balanced diet (AIN-93G) and a fructose group (F2; n 6) was fed on a purified 60 % fructose diet. Finally, two young rat groups (aged 28 d) were analysed: a control group (C3; n 6) was fed on the AIN-93G diet and a fructose group (F3; n 6) was fed on a 60 % fructose diet. After 4-8 weeks, the animals were evaluated. Glucose tolerance, peripheral insulin sensitivity, blood lipid profile and body fat were analysed. In the fructose groups F2 and F3 glucose tolerance and insulin sensitivity were lower, while triacylglycerolaemia was higher than the respective controls C2 and C3 (P < 0.05). Blood total cholesterol, HDL and LDL as well as body fat showed change only in the second protocol. In conclusion, high fructose intake is more effective at producing the signs of the metabolic syndrome in adult than in young Wistar rats. Additionally, diet seems to be a more effective way of fructose administration than drinking water.
Keywords: Body fat; Fructose; Insulin sensitivity; Metabolic syndrome; cholesterol; drinking water; fructose; high density lipoprotein cholesterol; lipid; low density lipoprotein cholesterol; triacylglycerol; age distribution; animal experiment; animal model; body fat; carbohydrate intake; cholesterol blood level; controlled study; experimental rat; food analysis; food composition; fructose metabolism; glucose tolerance; hypertriglyceridemia; insulin sensitivity; lipid blood level; male; metabolic balance; metabolic syndrome X; nonhuman; rat; triacylglycerol blood level; Wistar rat; Animals; Blood Glucose; Cholesterol; Disease Models, Animal; Glucose Tolerance Test; Insulin; Insulin Resistance; Male; Metabolic Syndrome X; Rats; Rats, Wistar; Weight Gain; Animalia; Rattus; Rattus norvegicus; Rodentia